2004
DOI: 10.1590/s1516-35982004000100001
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do fotoperíodo sobre o desenvolvimento de girinos de rã-touro (Rana catesbeiana Shaw, 1802)

Abstract: RESUMO -O objetivo deste trabalho foi avaliar o efeito de diferentes fotoperíodos sobre o peso, comprimento e a metamorfose de girinos de rã-touro (Rana catesbeiana Shaw, 1802). Foram utilizados 720 animais de uma mesma desova, no estágio 25, segundo Gosner (1960), distribuídos em 24 caixas de polietileno, com 30 litros de volume d'água, resultando em uma densidade de 1 girino por litro. Os tratamentos consistiram em seis fotoperíodos [0L:24D; 8L:16D; 12L:12D; 14L:10D (natural, como testemunho); 16L:8D e 24L:0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 10 publications
2
13
0
6
Order By: Relevance
“…Evaluations that include temperature (Figueiredo et al, 1999;Tavares-Braga and Lopes-Lima, 2001), photoperiod (Bambozzi et al, 2004) and nutrition Olvera-Novoa et al, 2007) are examples of work done in this field. In addition, stocking density is also an important factor in tadpole stage (Martínez et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Evaluations that include temperature (Figueiredo et al, 1999;Tavares-Braga and Lopes-Lima, 2001), photoperiod (Bambozzi et al, 2004) and nutrition Olvera-Novoa et al, 2007) are examples of work done in this field. In addition, stocking density is also an important factor in tadpole stage (Martínez et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Alguns trabalhos abordam o efeito de certas variáveis sobre o crescimento dos girinos, como o fotoperíodo (Bambozzi et al, 2004), densidade de estocagem Hayashi et al, 2004), temperatura (Braga & Lima, 2001) e níveis protéicos Braga et al, 1998).…”
Section: Introductionunclassified
“…Photoperiod was the best predictor of calling activity for anuran assemblages in subtropical regions (Both et al 2008, Kaefer et al 2009, Canavero and Arim 2009. Bambozzi et al (2004) demonstrated that this variable is positively related to weight gain and metamorphosis rates of L. catesbeianus tadpoles. In addition, Figueiredo et al (2001) showed that photoperiod is responsible for reproductive organ development in this species in captivity.…”
Section: Discussionmentioning
confidence: 94%